2021
DOI: 10.1007/s11101-021-09750-8
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting nature: a review of iridoids as a potential antileishmanial class

Abstract: Leishmaniasis still stands as one of the most prevalent neglected tropical diseases in the least developed and emerging countries. The recommended therapeutic arsenal to treat leishmaniasis is characterized by several shortcomings, and resistance has already been reported. Hence, this dramatic background highlights the pressing need to develop novel, affordable, and safe antileishmanial drugs. Multiple classes of natural compounds have been reported to possess antileishmanial activity. Among these classes, iri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 94 publications
0
2
0
1
Order By: Relevance
“…The tiliroside ( 6) is a ubiquitous flavonoid under this genus, and it is a compound with probed actions in different biological research (Luhata and Luhata, 2017;Grochowski et al, 2018). Regarding the sweroside (5) belonging to the iridoids, they are not common in the genus but are also metabolites with interesting results in investigations that trying to deal with biological activities (Hussain et al, 2019;Arraché-Gonçalves et al, 2021). The results here exposed shown that all the metabolites found in these two Ecuadorian medicinal plants, are considered under the chemotaxonomy of both genus, and they could be responsible for the medicinal properties attributed by the people to these species.…”
Section: Resultsmentioning
confidence: 99%
“…The tiliroside ( 6) is a ubiquitous flavonoid under this genus, and it is a compound with probed actions in different biological research (Luhata and Luhata, 2017;Grochowski et al, 2018). Regarding the sweroside (5) belonging to the iridoids, they are not common in the genus but are also metabolites with interesting results in investigations that trying to deal with biological activities (Hussain et al, 2019;Arraché-Gonçalves et al, 2021). The results here exposed shown that all the metabolites found in these two Ecuadorian medicinal plants, are considered under the chemotaxonomy of both genus, and they could be responsible for the medicinal properties attributed by the people to these species.…”
Section: Resultsmentioning
confidence: 99%
“…Leishmania-host interactions are considered to be excellent models of virulence factors, the efficiency of survival and transmission strategies over the life cycle, the ability to interact with the physiology and complex molecular mechanisms of the host cell, the modification of the cellular environment, the establishment of different niches, and modulation with the histopathological and immune responses of different hosts [20,38,63,64]. The uptake of the promastigotes by the phagocytes involves a number of different strategies that enable the parasite to interfere with the sequential protective actions of the two principal host immunological mechanisms [20].…”
Section: Host Leishmania Interactions Through Extracellular Productsmentioning
confidence: 99%
“…В ряде исследований у экстрактов, полученных из растений рода марьянник, выявлена антиоксидантная, антимикробная [10], цитотоксическая [11] активность. В последние годы биологическая активность индивидуальных веществ, выделенных из видов рода марьянник, изучается с целью создания потенциальных лекарственных средств для лечения трипаносомоза [12], лейшманиоза [13,14], а также оказывающих противовоспалительное действие [15].…”
Section: Introductionunclassified